Such Stuff As Diaspora Dreams Are Made On: Birobidzhan and the Canadian-Jewish Communist Imagination - Srebrnik, Henry (Canadian Jewish Studies / Études juives canadiennes, 2002)
This article examines the history of two organizations whosemain aim was to provide support for the Soviet project to establish a Jewish socialist republic, the official language of whichwas to be Yiddish, in the Birobidzhan region of the USSR.ICOR was founded in 1924 and was active within the Jewish,immigrant, working-class milieu; Ambijan, in Canada calledthe Canadian Birobidjan Committee, was formed in the UnitedStates in 1934. Both groups were ideologically and organizationallytied to the Communist Party of Canada and operatedfor some three decades. They became ideologically marginaland politically irrelevant during the Cold War, especially afterthe Birobidzhan project was exposed as largely fraudulent.Both groups disbanded in the 1950s.